Capturing economic and social value from hydrocarbon gas flaring and venting: evaluation of the issues - Etienne Romsom; Kathryn McPhail (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Atmospheric emissions urgently need to reduce for natural gas to fulfill its potential role in the energy transition to achieve the Paris Agreement on climate change. This paper establishes the magnitude and trends of flaring and venting in oil and gas operations, as well as their emissions and impact on air quality, health, and climate. While global flaring and venting comprise 7.5 per cent of natural gas produced, their combined impact on health and climate (in terms of Social Cost of Atmospheric Release) accounts for 54 per cent. Many low- and middle-income countries are economically dependent on oil and gas production. Most premature deaths from air pollution in 2016 were in developing countries. Most natural gas losses and emissions are avoidable. If all natural gas flared and vented globally is captured and brought to market, it could supply annually more than the total South and Central America gas consumption, plus all of Africa's power needs. If 75 per cent of these volumes are captured, it provides an additional natural gas sales value of US36 billion per annum (assuming an average gas price of US4/MMBtu).
Keywords: Q3; Q4; Q5; 330; energy transition; gas; health; climate; air quality